Brugia malayi gene expression in response to the targeting of the Wolbachia endosymbiont by tetracycline treatment. - Elodie Ghedin; Tiruneh Hailemariam; Jay V DePasse; Xu Zhang; Yelena Oksov; Thomas R Unnasch; Sara Lustigman (Public Library of Science (PLoS), 2009)
Brugia malayi, like most human filarial parasite species, harbors an endosymbiotic bacterium of the genus Wolbachia. Elimination of the endosymbiont leads to sterilization of the adult female. Previous biochemical and genetic studies have established that communication with its endobacterium is essential for survival of the worm.We used electron microscopy to examine the effects of antibiotic treatment on Wolbachia cell structure. We have also used microarray and quantitative RT-PCR analyses to examine the regulation of the B. malayi transcripts altered in response to the anti-Wolbachia treatment. Microscopy of worms taken from animals treated with tetracycline for 14 and 21 days (14 d and 21 d) demonstrated substantial morphologic effects on the Wolbachia endobacterium by 14 d and complete degeneration of the endobacterial structures by 21 d. We observed upregulation of transcripts primarily encoding proteins involved in amino acid synthesis and protein translation, and downregulation of transcripts involved in cuticle biosynthesis after both 7 d and 14 d of treatment. In worms exposed to tetracycline in culture, substantial effects on endobacteria morphology were evident by day 3, and extensive death of the endobacteria was observed by day 5. In a detailed examination of the expression kinetics of selected signaling genes carried out on such cultured worms, a bimodal pattern of regulation was observed. The selected genes were upregulated during the early phase of antibiotic treatment and quickly downregulated in the following days. These same genes were upregulated once more at 6 days post-treatment.Upregulation of protein translation and amino acid synthesis may indicate a generalized stress response induced in B. malayi due to a shortage of essential nutrients/factors that are otherwise supplied by Wolbachia. Downregulation of transcripts involved in cuticle biosynthesis perhaps reflects a disruption in the normal embryogenic program. This is confirmed by the expression pattern of transcripts that may be representative of the worms' response to Wolbachia in different tissues; the early peak potentially reflects the effect of bacteria death on the embryogenic program while the second peak may be a manifestation of the adult worm response to the affected bacteria within the hypodermis.